Legal recognition of gender identity in Latin America: reflections and lessons for the Spanish legal discussion - Cárdenas Cordón , Alicia (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
Spanish legal discussion on the rights of transgender people and the possible collision with other legally protected interests has been fuelled by the recent approval, by the Council of Ministers, of the draft Law for the real and effective equality of transgender people and for the guarantee of the rights of LGTBI people. In this context, this paper sets out to find out what the legal reality of trans people is beyond our borders, specifically, within the Inter-American Human Rights System, with the main aim of finding tools and interpretative keys which, from the legislation and legal conflicts of the countries analysed, provide lessons for the Spanish legal debate.
Keywords: transgender people; rights; discrimination; transgender minor